Effects of a physical-recreational activity program on reducing sedentary behavior indicators in middle school students (RIAF. International Journal of Physical Activity, 2026)
Abstract: Introduction: Sedentary behavior is one of the most telling signs of a decline in quality of life across different age groups, including children. Promoting physical and recreational activities at an early age is a priority in the school setting. Objective: To evaluate the effects of a physical-recreational activity program on reducing sedentary behavior indicators in middle school students. Methodology: A sample of 42 students (n=42) was used. The Body Mass Index (BMI), the International Physical Activity Questionnaire (IPAQ), and the Four by One-Day Physical Activity Questionnaire (CPAF) were administered. These instruments allowed researchers to determine body composition, the level of participation in physical activities, the number of hours dedicated to activities per day, and calorie consumption, thus revealing sedentary tendencies among the participants. Results: The proposed structured program of extracurricular activities led to significant changes in BMI, as demonstrated by the Wilcoxon signed-rank test (p-value = 0.02 < 0.05). The IPAQ was corroborated by the student’s t-test, which showed highly significant changes after the program's implementation (p-value = 0.000 < 0.005). The Wilcoxon test for CPAF also yielded p-values of 0.00 < 0.05 for the indicators of more intense physical activity. Conclusions: The program's implementation was effective, demonstrating highly significant results after its application in most indicators, thus confirming the research hypothesis.
Keywords: Extracurricular program; Physical-recreational activities; Sedentary lifestyle